A new strategy to tackle severe knee osteoarthritis: Combination of intra-articular and intraosseous injections of Platelet Rich Plasma. (3rd May 2016) - Sánchez, Mikel; Anitua, Eduardo; Delgado, Diego; Sanchez, Peio; Prado, Roberto; Goiriena, Juan Jose; Prosper, Felipe; Orive, Gorka; Padilla, Sabino
ABSTRACT: Introduction : Knee osteoarthritis (KOA) is a mechanically induced, cytokine and enzyme-mediated disorder involving all the joint tissue of the knee. Rebuilding a physiological-homeostatic network at the tissue level following knee organ failure, such as in severe KOA, is a daunting task with therapeutic targets encompassing the articular cartilage, synovium and subchondral bone. Intraarticular infiltration of plasma rich in growth factors (PRP) has emerged as a promising symptomatic approach, although it is insufficient to reach the subchondral bone. Areas covered : This review addresses current molecular and cellular data in joint homeostasis and osteoarthritis pathophysiology. In particular, it focuses on changes that subchondral bone undergoes in knee osteoarthritis and evaluates recent observations on the crosstalk among articular cartilage, subchondral bone and synovial membrane. In addition, we review some mechanistic aspects that have been proposed and provide the rationale for using PRP intraosseously in KOA. Expert opinion : The knee joint is a paradigm of autonomy and connectedness of its anatomical structures and tissues from which it is made. We propose an innovative approach to the treatment of severe knee osteoarthritis consisting of a combination of intraarticular and intraosseous infiltrations of PRP, which might offer a new therapeutic tool in KOA therapy.